Evaluation of staining techniques in the laboratory diagnosis of cryptosporidiosis (Brazilian Journal of Health Research, 2023)
Introduction: Cryptosporidiosis is a diarrheal disease that mainly affects children and immunocompromised individuals. Laboratory diagnosis is based on permanent staining techniques and many challenges still need to be overcome for its implementation as a routine in clinical laboratories. Objectives: Compare the effectiveness of different staining techniques in the detection of Cryptosporidium spp. in stool samples and evaluate the best methodology to be implemented in clinical laboratories. Methods: Individuals presenting clinical suspicion of cryptosporidiosis were invited to participate in the study. A total of 18 stool samples (with and without 10% formaldehyde preservative) were analyzed. Five different methodologies were performed: Ziehl-Neelsen (ZN) with and without heating, Safranina (SF) with and without heating and Panoptic Fast. Results: Of the 18 samples analyzed, seven (38.9%) were positive for Cryptosporidium spp. by at least one of the staining techniques used. Statistical agreement was “slight” (Kappa=0.36, p
Keywords: Cryptosporidium spp.; Permanent stains; Microscopy; Diagnosis; Quality control